Synthesis of Nb2O5 and Ta2O5 nanopowders by means of an endo-templating method. Issue 18 (15th December 2017) - Gibot, P.; Schnell, F.; Spitzer, D.
Abstract: Finding efficient templates for the nanostructuring of materials is a key point. Here, the niobium (V) - and tantalum (V) oxide ceramics nanopowders have been synthesized by a hard-templating approach by using the tricalcium phosphate biomaterial (Ca3 (PO4 )2 .xH2 O) as template agent. The oxide ceramics were investigated by X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, nitrogen physisorption and Scanning Electron Microscopy (SEM). It was observed that the surface properties (specific surface areas, pore volumes) of the Nb2 O5 and Ta2 O5 powders were strongly dependent of the amount of the Ca3 (PO4 )2 .xH2 O template previously used in the preparation of the [oxide ceramics/template] composites. For instance, with a Ca3 (PO4 )2 .xH2 O/ceramic salt weight ratio ranging from 0 to 1, the specific surface areas of Nb2 O5 and Ta2 O5 were gradually enhanced of 48–166 m 2 /g and 5–84 m 2 /g, respectively. The pore volumes were increased as well. The use of the eco-friendly tricalcium phosphate material (Ca3 (PO4 )2 .xH2 O) as template in the hard-templating approach may be suitable and efficient in the aim of synthesizing materials with enhanced surface properties.